Strengthening Digital Literacy and Internet Security Awareness for Sisingamngaraja XII Tapanuli University Students: Building Sustainable Policies and Practices in Higher Education Environments - Rekolina Siahaan; Response C. Tampubolon (International Journal of Community Engagement and Development, 2024)
In the ever-growing digital era, digital literacy and internet security awareness have become essential for students in facing the complex challenges of the digital world. This research aims to develop community service that focuses on strengthening digital literacy and internet security awareness in higher education environments. Through a collaborative approach between students, lecturers and campus administration, this program aims to build sustainable policies and practices to strengthen digital literacy and internet security awareness. Using a participatory methodology, the program engages students in a series of activities such as workshops, training and social campaigns to increase their understanding of key issues in digital literacy and internet security. Apart from that, this program also involves lecturers and campus administration in designing policies that support the integration of digital literacy in the academic curriculum and facilitate student access to relevant resources. It is hoped that the results of this program will create an educational environment that is safer and more responsive to digital challenges, so that students can become smarter and more responsible internet users. In addition, the experience gained from this program can become a basis for the development of similar initiatives in various higher education institutions, which will ultimately make a positive contribution to society as a whole in facing the ever-evolving digital era.